Detection Of Vibrio Parahaemolyticus In Shell Fish By Cultural And Polymerase Chain Reaction - N. SUBHASHINI; N. KRISHNAIAH; CH. BINDU KIRANMAYI (International Journal of Pharma and Bio Sciences, 2011)
A total of 105 shell fish samples (35 each of prawn, shrimp and crab) collected from local markets were subjected to cultural methods and PCR for the presence of V. parahaemolyticus and their toxins using primers for toxR, tdh and trh genes respectively. Out of total 105 samples, positive isolates of V. parahaemolyticus were found in 17 prawn samples, 25 shrimp and 19 crab samples by cultural method where as by PCR assay the organism was found in 24 samples of prawn, 33 shrimp and 27 crab samples. Out of 84 positive isolates of V. parahaemolyticus by PCR method, 11 showed presence of tdh, 37 had trh and 6 had both tdh and trh. Selective broths (Alkaline PeptoneWater and Salt Polymyxin Broth) were more efficient than non-selective broths (Brain Heart Infusion and Tryptic Soy Broth) and Salt Polymyxin Broth (SPB) was superior over Alkaline Peptone Water (APW) in selective broths for isolation of this organism by both cultural and PCR methods. The sensitivity of PCR method for this organism was 2.5cfu.